MODEL KONSELING MELALUI PERMAINAN SIMULASI UNTUK MENINGKATKAN KECERDASAN EMOSIONAL SISWA SEKOLAH MENENGAH PERTAMA : Studi Pengembangan Pada Siswa SMP Di Kota Malang - M Ramli, - (2007)
The service for the enhancement of junior high school students' emotional intelligence is very important. Nevertheless, the service implementation is not optimal yet because the effective counseling model is not found yet. Therefore, an effective counseling model through simulation games is developed for the enhancement of junior high school students' emotional intelligence.The main aim of this research is the completion of a counseling model through simulation games for the enhancement of junior high school students' emotional intelligence. The research uses an educational research and development design through major steps as follows (I) conducting a preliminary study, (2) designing a hypothetical counseling model through simulation games, (3) conducting a conceptual feasibility study of hypothetical counseling model through simulation games, (4) revising a hypothetical counseling model based on the conceptual feasibility study of the model, (5) conducting a field testing consisting of field feasibility testing and effectiveness testing, and (6) revising the model as a final counseling model through simulation games for the enhancement of junior high school students' emotional intelligence.Research subjects are public junior high school students and counselors in Malang. The data were collected by an inventory of junior high school students' emotional intelligence, interview guides, and self-evaluation. The data were analyzed by descriptive statistical analysis techniques, /-test, anova, and descriptive analysis techniques.In general, the research shows that the counseling model through simulation games is effective to enhance junior high school students' emotional intelligence because the enhancement of experimental group students' emotional intelligence is significantly higher than the enhancement of control group students' emotional intelligence.It is recommended that (1) the counseling model through simulation games should be implemented by counselors to enhance the public junior high school students' emotional intelligence in Malang, (2) the counseling model should be integrated into the course materials of group guidance and counseling and of inservice-training for counselors, and (3) further research should be done to enhance the quality of counseling model effectiveness for wider settings and various background of target population.